Scrum Methodology with Open Educational Resources in University Higher Education: Systematic Review in Spanish - Sotelo-Martín, José-Alberto (2023)
This work reviews the most relevant and current literature in Spanish about the combination between the use of open educational resources and the Scrum methodology as a way of organizing open educational materials intended to create final products in higher education. The methodology used in this work follows the PRISMA guidelines for systematic reviews, with a systematic publication search approach based on a series of different inclusion and exclusion criteria. The results of the review reveal a scarce development of research and teaching projects in which open educational resources and Scrum were combined. Finally, the review question that motivates this work is answered and it is concluded that there is no scope for this combined use in Spanish, as well as the desirability of continuing with the review in other languages, especially in English.